Examination of exercise-related health beliefs, kinesiophobia, and perceived stress across different rheumatological diagnostic groups - Ergün, Betül; Elbastı, Muhammet Şahin; Baglan-Yentur, Songul; Yamancan, Gülşah (Nurtekin ERKMEN, 2026)
Psychosocial factors such as exercise beliefs, kinesiophobia, and stress are important in rheumatic diseases. This study examined these variables across three clinical groups based on disease type. A total of 119 patients were enrolled and categorized into three groups as follows: (Group 1) Axial Inflammatory Diseases (n = 41), comprising individuals diagnosed with Ankylosing Spondylitis (AS, n = 23) and Behçet’s disease with axial involvement (n = 18); (Group 2) Peripheral/Systemic Autoimmune Diseases (n = 41), including Rheumatoid Arthritis (n = 30), Systemic Lupus Erythematosus (n = 5), and Systemic Sclerosis (n = 6); and (Group 3) Fibromyalgia Syndrome (n = 37). Participants completed the Perceived Stress Scale (PSS), Tampa Kinesiophobia Scale (TKS), and Exercise-Related Health Beliefs Attitude Scale (ERHBAS). Intergroup differences were analyzed using ANOVA, MANCOVA, and Kruskal-Wallis tests; correlations were assessed with Spearman’s rho. Significant differences were observed between groups in gender and smoking (p<0.001), but not in alcohol use (p=0.708). ERHBAS total and subscale scores were similar across groups (p>0.05). Age differed between groups (p=0.024), significant only between Groups 1 and 2. PSS scores were higher in Group 3 compared to Groups 1 and 2 (p<0.001), while TKS scores showed no group differences (p=0.844). Correlation analysis indicated positive associations of age with PSS (p=0.018) and TKS (p=0.006), and a negative association between ERHBAS and PSS (p=0.037). Perceived stress was higher in Group 3. Kinesiophobia was similar across groups and increased with age. Exercise-related beliefs were similar but decreased as stress increased. These results highlight the role of psychosocial factors in managing rheumatic diseases.
Keywords: Rehabilitation; Rehabilitasyon; Allied Health and Rehabilitation Science (Other); Yardımcı Sağlık ve Rehabilitasyon Bilimi (Diğer)